Screening and characterization estrogen receptor ligands from Arnebia euchroma (Royle) Johnst. via affinity ultrafiltration LC-MS and molecular docking - Zhu, Lian; Ma, Sheng-jun; Liu, Ming-juan; Li, Kai-lin; E, Shuai; Wang, Zi-ming; Li, Sha-ni; Zhang, Sheng-lan; Cai, Wei (Frontiers in Plant Science, 2022)
Arnebiae Radix (dried root of Arnebia euchroma (Royle) Johnst.) is a traditional Chinese medicine (TCM) used to treat macular eruptions, measles, sore throat, carbuncles, burns, skin ulcers, inflammations. Among then, Arnebiae Radix extract can exert anti-breast cancer effect through various mechanisms of action. This study aimed to screen potential estrogen receptor (ERα and ERβ) ligands from Arnebiae Radix extract rapidly. In this study, an analytical method based on affinity ultrafiltration coupled UHPLC-Q-Exactive Orbitrap mass spectrometry was established for rapidly screening and identifying estrogen receptor ligands. Moreover, bindings of the components to the active site of estrogen receptor (ERα and ERβ) were investigated via molecular docking. As a result, a total of 21 ligands were screening from Arnebiae Radix using affinity ultrafiltration. And each ligand could have a good affinity for the multiple amino acid residues of estrogen receptor based on molecular docking. The method established in the study could be used to rapidly screen estrogen receptor ligands in Traditional Chinese medicine. The results demonstrated that affinity ultrafiltration UHPLC-Q-Exactive Orbitrap mass spectrometry method not only aid in the interpretation of the potential bioactive components and possible mechanisms of action of Arnebiae Radix, but also provide a further effective basis for the quality control of this valuable herb medicine.